Species determination of Malaysian Bactrocera pests using PCR-RFLP analyses (Diptera Tephritidae) - Tock, Hing Chua; Yi, Vern Chong; Saw, Hoon Lim (John Wiley & Sons, Ltd, 2010)
Identification of Bactrocera carambolae Drew and Hancock, B. papayae Drew and Hancock, B. tau Walker, B. latifrons Hendel, B. cucurbitae Coquillett, B. umbrosa Fabricius and B. caudata Fabricius would pose a problem if only a body part or an immature stage were available. Analysis of polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) of cytochrome oxidase I (COI) gene using primers COIR, COIF, UEA7 and UEA10 and restriction enzymes (MseI, RsaI and Alu1) was carried out. The banding profiles in the electrophoresis gel were analysed. The COI gene in six Bactrocera spp. was successfully amplified by COIR and COIF, as well as UEA7 and UEA10, while B. caudata was amplified successfully only by UEA primers. Using COI amplified PCR products and restriction enzymes, distinct banding profiles for B. tau, B. latifrons, B. cucurbitae and B. umbrosa were observed, but not for B. carambolae and B. papayae. However, using UEA7, UEA10 and RsaI, B. caudata could be identified, while B. carambolae and B. papayae might possibly be separated from one another. It was also shown that adult body parts or immature life stages of B. carambolae, B. papayae, B. latifrons and B. cucurbitae produced the same banding profiles as the adults. PCR-RFLP analyses are able to identify positively five Bactrocera species, while B. papayae and B. carambolae might possibly be separated from one another, even if immature life stages or adult body parts are used.